Corrigendum: Environmental Impacts of Plant-Based Diets: How Does Organic Food Consumption Contribute to Environmental Sustainability? - Lacour, Camille; Seconda, Louise; Allès, Benjamin; Hercberg, Serge; Langevin, Brigitte; Pointereau, Philippe; Lairon, Denis; Baudry, Julia; Kesse-Guyot, Emmanuelle (Frontiers in Nutrition, 2018)
Corrigendum